Group Acceptance Sampling Plan Based on Power Lindley Distribution and Application for Lifetime Data - Yimnak, Kanittha; Yimnak, Kannika; Kaewumpai, Supanut (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2022)
A group acceptance sampling plan (GASP) for product lifetime data based on power Lindley distribution (PLD) was proposed along with the minimum group sizes, operating characteristic function values, the minimum ratios for the producer’s risk = 0.05 under different conditions. In addition, the proposed GASP was applied to an actual data. The results showed that the proposed GASP could efficiently determine whether to accept or reject the product. In addition, the presented group acceptance sampling plan provided a minimum sample size for testing the product quality with a higher specified number or the greater a.